Aproposed Framework for International Mine Action Standard of Quality Management Case Study on Geneva International Center Humanitarian Demining - El-shahat, Nehal; Albetagy, Aymen; Khalifa, Ahmed (The Arab Journal of Administration, 2024)
The research aims to try to present a concept of quality management and the application of international standards in mine action activities, which include demining operations, assisting the injured and families of victims of mine explosion accidents and remnants of war, and mine risk education in order to reduce casualties and improve the quality of life. The study is based on a case study on the Geneva International Center for Humanitarian Demining in Switzerland, the center provides operational, scientific and technical assistance, procedures, dissemination of knowledge, improvement of management, quality assurance, information systems management, and care for the mine-related media in accordance with international standards and documents supporting international law with the aim of raising the professionalism of mine-related actions around the world. The study relied on the appropriate approach to the study, The researchers used a survey list prepared for purpose of collecting data according to the study variables, also used Alpha. Researchers used a sample of 39 individuels from 9 countries. The study concluded with several results, the most prominent of which is the effect of managing the quality of international standards in mine action, and then proof of the validity of the assumption and the existence of a statistically significant negative impact on managing the quality of standards in mine action activities, as there is an impact of managing the quality of international standards in mine action in all activities, which include Mine clearance operations, assistance to survivors and families of mine victims, and mine risk education programs. The study recommends the need to improve the performance of national authorities working in the field of mine action, national authorities, mine action centers, and international, regional and local organizations working in the field of mine action. The study also recommends the necessity of developing the management system and quality management, ensuring quality management, updating and developing management systems in accordance with international standards. Taking into account the review of relevant international agreements and treaties, enactment of legislation and laws that regulate all mine-related actions in accordance with international standards, taking into account the periodic review of all that is needed and the new information and data related to clearance operations and operations to assist the injured and victims' families, and improving the performance of mine risk education programs in accordance with international standards.